2013
DOI: 10.1007/s10840-013-9851-1
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged P-wave duration is associated with atrial fibrillation recurrence after successful pulmonary vein isolation for paroxysmal atrial fibrillation

Abstract: The presence of pre-existent prolonged PWD is associated with a higher risk of AF recurrence post PVI for paroxysmal AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 22 publications
3
73
0
1
Order By: Relevance
“…17,18 The delayed and heterogeneous activation of the LA results in dispersion of atrial refractory periods, interatrial dyssynchrony and impaired LA mechanical function, 19,20 all of which favor the development of AF. Thus, IAB (partial or advanced) has been found to be associated with new-onset AF in patients from a general hospital population, 21 , recurrence of AF postelectrical or pharmacological cardioversion, 22,23 , AF recurrence after pulmonary vein isolation, 24 and progression of paroxysmal AF to the persistent or permanent forms of the disease. 25,26 In patients with CHF, the association of Pwave abnormalities with development of AF was first described by Yamada et al 15 using signal averaged ECG (SAECG).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The delayed and heterogeneous activation of the LA results in dispersion of atrial refractory periods, interatrial dyssynchrony and impaired LA mechanical function, 19,20 all of which favor the development of AF. Thus, IAB (partial or advanced) has been found to be associated with new-onset AF in patients from a general hospital population, 21 , recurrence of AF postelectrical or pharmacological cardioversion, 22,23 , AF recurrence after pulmonary vein isolation, 24 and progression of paroxysmal AF to the persistent or permanent forms of the disease. 25,26 In patients with CHF, the association of Pwave abnormalities with development of AF was first described by Yamada et al 15 using signal averaged ECG (SAECG).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 It has been independently associated with incident AF 8,1012 and recurrent AF after pulmonary vein isolation. 9 Prospective cohort studies have demonstrated that incident AF carries an independent risk of death from cardiovascular disease and all causes. 2,19 AF can reduce the threshold for ventricular arrhythmias by directly reducing refractoriness 20 and generating pro-arrhythmic short-long-short sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Pwd is an electrocardiographic marker associated with inhomogeneous and discontinuous propagation of sinus impulses (5). Prolonged P-wave duration and increased Pwd have been reported to carry an increased risk of atrial fibrillation (AF) (6). QT dispersion (QTd) can be used to assess the homogeneity of cardiac repolarization (7).…”
Section: Introductionmentioning
confidence: 99%